Molecular Systematics of the Long-Snouted Deep Water Dogfish (Centrophoridae, Deania) With Implications for Identification, Taxonomy, and Conservation - Stefanni, Sergio; Catarino, Diana; Ribeiro, Pedro A.; Freitas, Mafalda; Menezes, Gui M.; Neat, Francis; Stanković, David (Frontiers in Marine Science, 2021)
According to the most recent taxonomical revision, the deep-sea dogfish genus Deania encompasses four species. Three of them, D. calcea, D. profundorum and D. hystricosa, occur in the North Atlantic. Whilst D. profundorum can be identified by the presence of a subcaudal keel, the other two species are not easily visually distinguished. Uncertainties over identification raises concerns over stock units and whether management plans are adequate. In this study we compared onboard visual identification of Deania specimens, with morphological inspection of skin denticles under stereo microscope and with independent molecular taxonomical assignment using two molecular markers. Particular emphasis was paid to specimens identified as D. calcea and D. hystricosa in the NE Atlantic where these species potentially occur sympatrically and may be easily confused. In the past the species have been discriminated on the basis of the size of skin denticles (skin roughness), but our study showed that the crown length of skin denticles covaries with size (and sex), irrespective of species, and therefore this is not a reliable morphological character and should not be used to discriminate between the two species. Phylogenetic analyses did not indicate that D. hystricosa to be a distinct lineage from D. calcea. Interestingly, however four individuals (specimens from: UK, Azores Is., Madeira Is. and Seine seamount) formed a well-defined sub-clade nested within the D. calcea clade, possibly a signature of a past vicariance event or a result of coalescent stochasticity..